2018
DOI: 10.1111/aogs.13360
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parity on risk of complications in pregnant women with epilepsy: a population‐based cohort study

Abstract: Second births in women with epilepsy do not represent an increased risk of non-iatrogenic complications, independent of antiepileptic drug use. There is a significant reduction in complications from first to second births in women with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…However, multivariate analysis found that gravidity was not an independent risk factor and the impact of HDP was only marginally significant. These results are similar to other studies 17 28–30. It was noteworothy that an abnormal quantity of amniotic fluid was the greatest risk factor affecting EmCS, followed by spontaneous seizure or induction of labor.…”
Section: Discussionsupporting
confidence: 91%
“…However, multivariate analysis found that gravidity was not an independent risk factor and the impact of HDP was only marginally significant. These results are similar to other studies 17 28–30. It was noteworothy that an abnormal quantity of amniotic fluid was the greatest risk factor affecting EmCS, followed by spontaneous seizure or induction of labor.…”
Section: Discussionsupporting
confidence: 91%
“…As preterm birth and caesarean delivery, to some extent, depend upon obstetric management, we strived to disentangle the effects of PsA from obstetric factors and especially parity, by restricting the analysis to first pregnancies to exclude the effect of obstetric management due to earlier pregnancy outcomes . In this analysis we found increased risks of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that women with AMA had higher incidences of pregnancy complications, such as hypertensive disorders of pregnancy, gestational hypertension, placental disorders, preterm labor, maternal near miss, and maternal death [ 4 7 ]. Moreover, research also suggested that the elevated risks of pregnancy complications in AMA may differ by parity [ 8 ], and inconsistent results were reported regarding certain complications [ 9 11 ]. For instance, some studies found that the risk of gestational diabetes and hypertensive disorders of pregnancy were increased in both nulliparous and multiparous women with AMA [ 9 ], while in some studies the increased risks for the two complications were not observed in both nulliparas and multiparas [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%